Character Education Based on the Contextualization of Keroncong Music - Kristanto, Alfa; Sunarto, Sunarto; Utomo, Udi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to analyze the form of character education emerging from the contextualization of keroncong music in GIA Dr.Cipto Semarang. The study employs a qualitative field research approach using a case study design, focusing on the musical practices of Orkes Keroncong Irama Surgawi. Data sources consisted of church music coordinators, keroncong trainers, musicians, congregational members, and documentation related to liturgical and musical activities. Data were collected through participant observation, in-depth interviews, and documentation, and then analyzed descriptively and interpretatively using Stephen Bevan’s anthropological contextualization model. The findings reveal that the contextualization of keroncong music functions not only as cultural preservation but also as a medium for character education embedded in communal musical practices. The identified character values include cultural awareness, nationalism, discipline, responsibility, cooperation, solidarity, tolerance, creativity, adaptability, perseverance, and appreciation of art. In addition, keroncong music also serves as a cultural bridge that strengthens interreligious and multicultural relationships in society. This study concludes that contextualized local music practices contribute significantly to the development of humanistic, religious, and cultural grounded character education.